Impact of Work Stressors on Career Commitment – A Study of Indian IT Sector Employees - Deshpande, Rohan; Chakraborty, Debarun (Prabandhan: Indian Journal of Management, 2023)
Purpose : The present article aimed to explore the impact of IT work stressors on the career commitment of Indian IT sector employees. The main goals were to study the effects of major stressors on job satisfaction and how they affected ITians’ motivation to pursue their careers, as well as to propose an explanatory model that evaluates the predictors of ITians’ career commitment through the lenses of major stressors from the body of existing literature. Methodology : Based on theories of conservation of resources, job satisfaction, and integrated model of career change, a research model was designed. A structured questionnaire was rolled out using convenience sampling and snowballing techniques to various Indian IT sector employees. Three hundred fifty-two complete responses were received. The hypotheses were validated using structural equation modeling in Amos. Findings : The findings showed that ITians’ career commitment was adversely impacted due to job dissatisfaction and prevailing stressful working conditions resulting from job insecurity and heavy perceived workload. Practical Implications : This study underscored that persistent stressful operating conditions can enervate IT employees and their engagement levels, not only with their jobs but also with their careers. It provides a useful counsel for HR departments and IT employees, emphasizing the need to strike the right balance between health and work objectives to allow the repletion of drained resources quickly to remain pursuant to the desired roadmap of a successful career. Originality : To our knowledge, no prior study had attempted to explore the implications of Indian IT employees’ stressful dispositions toward their motivation to remain associated with this career field, and the same was the principal scope of this research.